Njaum-Njaum As A Marriage Proposal Of Kedayan’s Ethnic Perspective Sarawak Islam Family Law Ordinance 2001 - Barwi, Normiwati Binti (Sakina: Journal of Family Studies, 2023)
Njaum-njaum tradition as a usual event of propose marriage in Kedayan’s ethnic. This tradition was initiated by the giving of a ring and cash money by the men to the woman as a pembuka mulut. The amount of this opening money is not fix, but it is subject to the request of the woman. Nowadays, people look less appropriate about this tradition. This research belongs to the type of empirical research, using a qualitative descriptive approach. The researcher was collected the primary data from direct interviews with informants from the community in Kampung Bungai, Bekenu town in Province of Sarawak, Malaysia. The secondary data was collected from literature books, papers, and articles relevant and related. This study shows the implementing process of njaum-njaum tradition of Kedayan’s ethnic that still practice until nowadays. They has their own reasons why they need to maintain this tradition. Based from what has been written on Sarawak Islamic Family Law Ordinance 2001, whoever have already entered into marriage propose or engagement agreement, and if one of them reneges, then they cancelled the marriage proposal and engagement can report to the Syariah Court for action and penalty. Keyword: Njaum-njaum; Tradition; Marriage.